A Critical Perspective on James Cone and US Black Liberation Theology: Exploring the Greatest Debate for Global Africana Religions That Never Happened. Issue 1 (2nd January 2021) - Azibo, Daudi Ajani ya
Abstract: There is an important debate which never took place among United States Black Liberation Theology (BLT) practitioners, including James Cone: about whether or not Black Liberation Theology should continue to be delimited in canon to that handed down from the lineage initiated by Constantine versus developing canon from historical and cultural deep thought of African civiliations. In this article it is argued that this is pivotal for its future. The necessity of a reversion to centred African-based religion as against the continuation of conversion to Western-based Judaism, Christianity, and Islam, is promoted. Mental disorder purveyed through religion (theological misorientation) is presented and BLT is redefined as favourable to the African Renaissance.